CHANGE IN URGENCY STATUS AMONG ULCERATIVE COLITIS PATIENTS: UNDERSTANDING THE IMPACT OF TREATMENT CHANGES FROM THE COREVITAS INFLAMMATORY BOWEL DISEASE REGISTRY. (22nd January 2022) - Wolf, Douglas; Naegeli, April; Moore, Page; Janak, Judson; Crabtree, Margaux; Shan, Mingyang; Hunter, Theresa; Sontag, Angelina; Cross, Raymond
Abstract: BACKGROUND: Stooling urgency (also known as urgency to defecate) is one of the most common symptoms among Ulcerative Colitis (UC) patients (pts). Understanding factors associated with changes in urgency status, such as the association between timing of treatment changes and subsequent onset or resolution of urgency symptoms, are essential in addressing unmet pts needs. Our aim was to explore treatment frequency and persistence among UC pts stratified by a change in urgency status from enrollment to the 6-month follow-up (6M) visit. METHODS: Participants included UC pts in the CorEvitas Inflammatory Bowel Disease Registry between 5/3/17-9/1/20. Stooling urgency was defined as no urgency or urgency using the categories, none and hurry/immediate, from the Simple Clinical Colitis Activity Index (SCCAI). Urgency status groups were formed by urgency at enrollment and the 6M visit: no persistent urgency (NPU), i.e., no urgency at both visits; change from urgency to no urgency (UN); change from no urgency to urgency (NU); and persistent urgency at both visits (PU). Chi-square tests were conducted to compare treatment use and change between urgency status groups (NPU=reference group). Kaplan Meier curves and log-rank tests were used to assess time to first treatment change between urgency status groups. RESULTS: The urgency status groups (n=400) included: 44% NPU (n=175), 21% UN (n=86), 14% NU (n=56), and 21% PU (n=83). A higher proportion of UN (47%, p=0.03) and PU (51%, p=0.01) pts received two or more treatments compared to NPU (33%) pts. Compared to NPU pts, pts in all three groups, UN (52% vs. 27%, p< 0.001), NU (45% vs. 27%, p=0.02), and PU (53% vs. 27%, p< 0.001) were more likely to change treatment between enrollment and the 6M visit. Similarly, a higher proportion of pts on a biologic at enrollment, UN (24% vs. 11%, p=0.01), NU (23% vs. 11%, p=0.03), and PU (35% vs 11%, p< 0.001), changed treatment between enrollment and the 6M visit vs. NPU pts. The time to first treatment change was shorter for all other urgency status groups when compared to NPU pts (log-rank tests, all p<0.02) (Figure 1). Among pts without urgency at enrollment, the time to first treatment change was shorter for NU vs. NPU pts (p=0.01) whereas it was similar for pts with urgency at enrollment, UN vs. PU pts (p=0.93) (Figure 1). CONCLUSION: Among UC pts in a real-world setting, there were significant differences in change of treatment and time to treatment change between pts who experienced urgency either at their enrollment visit, 6M, or both, compared to those without urgency. Urgency at any time point is a symptom of great concern to UC pts, is a sign of inadequate therapy, and often is an indication to switch treatment therapy.